Edukasi Kesehatan Reproduksi Tentang PCOS Pada Remaja - Hamdiyah Hamdiyah; St. Nurbaya; Syahriani Syahriani; Fitriani Fitriani; Ibrahim Ibrahim; Rusdiana Rusdiana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
Teenagers are the next generation of the nation. Adolescent girls in their life cycle experience menstruation. Menstruation is a natural cycle that occurs in a woman's body. Some women experience disturbances in the process of the menstrual cycle. So that every woman should know the problems that occur in her body so that early detection of accompanying diseases can be carried out. This activity aims to provide information and increase youth knowledge about reproductive health and PCOS. This educational process uses the lecture method with the help of leaflets. The results obtained from this activity are that young women understand reproductive health, especially menstruation and PCOS and understand the importance of early detection. The assessment is based on the response and enthusiasm of the participants in receiving the material provided. Including the positive response of participants in answering questions correctly when asked questions by the speaker.